Pelatihan Penyusunan Perangkat Pembelajaran Anak Usia Dini Bagi Guru-Guru Paguyuban POS PAUD di Wilayah Tlogomas - Yulianti S; Prihatin Sulistyo (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
Based on the results of monitoring of learning at Post PAUD in Tlogomas region in the 20172018 semester, there are several findings in the development of non-formal education institutions among the following; 1). facilities and learning infrastructure that has not been good, 2). The welfare of teachers is still uncertain, 3). administrative demands from partner institutions, and also 4). different curriculum guide of ECD (Formal) with Post PAUD (non Formal), also related teacher competence. This devotion program helps provide partner problem solving that is; mentoring and training of learning tool preparation, the planning stage begins with visits to several PAUD Post. Implementation of each teacher reviewing learning tools, dilanjudkan accompaniment team as well as training the preparation of personal RPPH preparation, then the results are presented in groups to get input repair and end the evaluation with the team of servants. The results of the teacher program can demonstrate the results of the group's work to make the RPPH hope that the follow-up of this activity will be dilanjudkannya in their respective institutions to improve the quality of learning according to student development.